Allpass section-based mixed-mode quadrature sinusoidal oscillator - Kumngern, Montree; Lamun, Panit (My University, 2013)
This paper presents a new electronically tunable mixed-mode quadrature sinusoidal oscillator using new allpass section as an building block. The oscillator is consisted of two allpass sections. Each allpass section employs one current-controlled current differencing transconductance amplifier and one grounded capacitor. The condition of oscillation and the frequency of oscillation can be controlled independently and electronically by adjusting the bias currents. The oscillator also offers two explicit quadrature voltage and quadrature current outputs into a single topology. The workability of the proposed structure is verified by PSPICE simulators based on 0.25 μm TSMC CMOS process. © 2013 IEEE.
Keywords: allpass section; current-controlled current differencing transconductance amplifier; mixed-mode circuit; quadrature sinusoidal oscillator